Mechanical characterization of polymer parts produced via multi-jet printing and fused deposition modelling - Wahid, Zaliha (2021)
Layer by layer additive manufacturing techniques have inherently low strength in z-orientation. Mechanical properties of the final products are influenced by both materials and processing method utilized. The multijet 3D printing technique is not new in Additive Manufacturing. Studies on the processing and product optimization are still ongoing. However, studies on the characterization of fabricated products using this technique has not yet been fully explored. Additionally, the said attributes might be distinctive depending on machine brand and manufacturer. Therefore, the main objective of this study is to investigate the effects of orientation by conducting mechanical and structural testing involving tensile strength, compression, flexural strength, and surface roughness at various orientations. Specimens of liquid resin VisiJet M3 Black materials were printed using ProJet 3510 HD by 3D Systems. For each test, specimens were prepared in three different orientations which were x-orientation, y-orientation, and z-orientation. To support the findings and to rule out material influences, tensile testing was performed using comparable materials but with a different printing technique, Fused Deposition Modelling (FDM). As an end use product, it is necessary to characterize fatigue behaviour and effect of orientation to structural integrity. In the fatigue test, specimens of each orientation underwent dynamic loading for fatigue life and fatigue properties. Another objective of this study is to characterize interconnecting layers and to relate how printing orientation may influence product performance. To achieve the objectives, a literature review on jetting and ultraviolet curing methods was carried out. Finally, the objective is to analyse the correct parameters reflected to product quality printed using ProJet 3510 HD. It was found that printing using ProJet 3510 HD had a significant effect to the mechanical strength at the x-orientation. From tensile testing, as compared to the x-orientation, the strength of the y-orientation was higher by 22%. While the strength showed only 6% difference as compared to the low strength z-orientation. These results was supported by the flexural test where the ultimate flexural stress at the y-orientation was almost four times higher than that of the x-orientation. Fracture surface microstructure. observations explained interconnection layers, failure characteristics, and effects of orientation. From this study, fatigue life data for specific materials, machine, and orientation has been discovered for future reference.